2012
DOI: 10.11594/jtls.02.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Hydro- Chemical Evolution of Palk Strait Region, Bay of Bengal

Abstract: Analysis was carried out on the physico-chemical parameters measured at two stations, Thondi and Soliyakudi in the southeast Palk Strait region during the monsoon and post monsoon seasons (November 2008-March 2009). High temperature (31˚C) and salinity (35%o) were recorded in the month of March (post monsoon). During the monsoonal season, dissolved oxygen content was found to be high (5.2 O2 mg l-1) and the total phosphorous concentration when compared to other nutrients such as NO3, NO2 and SiO2, was also hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Heavy metals are naturally present in the soil and cannot be degraded, they can remain in the soil and water bodies for a long time, so they will continue to increase over time [12]. The accumulation of metals in the soil can decrease soil microbial activity, soil fertility, overall soil quality, and a decrease in yields and the entry of toxic materials into the food chain [13].…”
Section: Results Of Analysis Of Heavy Metals In Soilmentioning
confidence: 99%
“…Heavy metals are naturally present in the soil and cannot be degraded, they can remain in the soil and water bodies for a long time, so they will continue to increase over time [12]. The accumulation of metals in the soil can decrease soil microbial activity, soil fertility, overall soil quality, and a decrease in yields and the entry of toxic materials into the food chain [13].…”
Section: Results Of Analysis Of Heavy Metals In Soilmentioning
confidence: 99%
“…Its boundary is bounded by the Gulf of Mannar, Pamban Island, Adam's (Rama's) Bridge, and Mannar Island. The southwest part of the strait is also known as Palk Bay [25]. The strait is less than 100 m deep, 64 to 135 km wide, and 137 km long.…”
Section: Methodology 21 Study Area and Geologic Contextmentioning
confidence: 99%
“…In Ghana and elsewhere, farming occurs near these mines (Essumang et al 2007), and arsenic (As), cadmium (Cd), and other contaminants have been observed in these soils which can then be absorbed by crops (Essumang et al 2007; Bempah and Ewusi 2016). Both Cd and As are highly harmful contaminants in the environment that lead to heavy metal pollution of soil and water due to natural weathering of geological materials, industrialization, pesticides, fertilizers, mining, and manufacturing (Garelick et al 2009; Govindasamy et al 2011; Ozbek et al 2014; Amel et al 2016). Due to their ability to accumulate through the food chain, Cd and As can adversely affect humans (Essumang et al 2007; Reeves and Chaney 2008; Huang et al 2017; Shahid et al 2017) where chronic Cd and As exposure has been connected to cancer and several other diseases (Reeves and Chaney 2008; Järup and Akesson 2009; Jomova et al 2011; Kamunda et al 2016; Huang et al 2017; Shahid et al 2017; Ayangbenro and Babalola 2017).…”
Section: Introductionmentioning
confidence: 99%